2002
DOI: 10.2754/avb200271020255
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Hygienic Quality of Vacuum-packed Pork during Storage

Abstract: Nápravníková E., L. Vorlová, L. Malota: Changes in Hygienic Quality of Vacuumpacked Pork During Storage. Acta Vet. Brno 2002, 71: 255-262. Hygienic quality of boned vacuum-packed pork was monitored during storage by sensory, chemical, and microbiological methods. Pork was vacuum-packed into polyamide/polyethylene (PA/PE) foil 72 h after slaughter. Initial temperature did not exceed 9°C. The meat was stored at 2.5 ± 0.5°C in the dark for 35 days and samples for laboratory examinations were collected at days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
(4 reference statements)
0
4
0
Order By: Relevance
“…Therefore, they may be more influenced by the absence of glucose stores than some other spoilage microorganisms that can metabolize numerous amino acids to supplement their energy needs. While LAB did not dominate the spoilage microflora in our study, Napravnikova and others (2002) determined that Lactobacillus curvatus and L. xylosus were the chief spoilage microorganisms of vacuum‐packaged sliced pork loin of varying pHu stored for 35 d in the dark at 3 °C. However, they showed that only pork with a pHu of 5.8 to 5.95 had a vacuum‐packaged shelf life of up to 28 d as determined by the production of off‐odors, discolored exudative juice, and bacterial induced discoloration.…”
Section: Resultsmentioning
confidence: 54%
“…Therefore, they may be more influenced by the absence of glucose stores than some other spoilage microorganisms that can metabolize numerous amino acids to supplement their energy needs. While LAB did not dominate the spoilage microflora in our study, Napravnikova and others (2002) determined that Lactobacillus curvatus and L. xylosus were the chief spoilage microorganisms of vacuum‐packaged sliced pork loin of varying pHu stored for 35 d in the dark at 3 °C. However, they showed that only pork with a pHu of 5.8 to 5.95 had a vacuum‐packaged shelf life of up to 28 d as determined by the production of off‐odors, discolored exudative juice, and bacterial induced discoloration.…”
Section: Resultsmentioning
confidence: 54%
“…In this study, the muscle reached pH u after 1 day postmortem. The reason may be the way of vacuum packing, which made the rate of lactate increase quickly (Napravnikova et al ., ). In addition, pH u from the PM muscle was higher than that of the LL and SM muscles ( P < 0.05).…”
Section: Resultsmentioning
confidence: 97%
“…5(d), the NH 3 concentration in fresh box was less than 0.5 ppm. According to the description in literature [75], the pork was completely inedible when NH 3 concentration exceeded 16 ppm during storage, which suggested that the pork was still in freshness at the moment. The gas sensor's response value reached 12.5% after 60 h of storage, showing the NH 3 concentration had reached 2.5 ppm at that point.…”
Section: Practical Application Of the Devicementioning
confidence: 99%